2015
DOI: 10.1111/mmi.13124
|View full text |Cite
|
Sign up to set email alerts
|

Non‐equivalent roles of two periplasmic subunits in the function and assembly of triclosan pump TriABC from Pseudomonas aeruginosa

Abstract: In Gram-negative bacteria, multidrug efflux transporters function in complexes with periplasmic membrane fusion proteins (MFPs) that enable antibiotic efflux across the outer membrane. In this study, we analyzed the function, composition and assembly of the triclosan efflux transporter TriABC-OpmH from Pseudomonas aeruginosa. We report that this transporter possesses a surprising substrate specificity that encompasses not only triclosan but the detergent SDS, which are often used together in antibacterial soap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In the asymmetric MFP dimer TriAB, these two functions were previously assigned to TriB and TriA, respectively (11). In this study, site-specific mutagenesis and disulfide cross-linking experiments showed that TriB predominantly binds to the H4-H7 interprotomer groove of OpmH and promotes opening of the channel, thus coupling the opening of the channel to the stimulation of the transporter.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the asymmetric MFP dimer TriAB, these two functions were previously assigned to TriB and TriA, respectively (11). In this study, site-specific mutagenesis and disulfide cross-linking experiments showed that TriB predominantly binds to the H4-H7 interprotomer groove of OpmH and promotes opening of the channel, thus coupling the opening of the channel to the stimulation of the transporter.…”
Section: Discussionmentioning
confidence: 84%
“…To confirm the functionality of OpmH His , JWW9 (attTn7:: P BAD -opmH His ⌬ompH::Gm) cells were transformed with the pBSPII vector and its derivatives pPS1824 and pBSPII-AxBC, which express the native TriABC pump and the covalently linked TriAxB protein along with TriC, respectively, from the constitutive P lac promoter (11). A covalent linkage between TriA and TriB ensures that the proteins are produced in equal quantities and assemble stoichiometric complexes with TriC and OpmH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been proposed that some bacterial efflux pumps require two different PAPs for functional activity, namely the TriABC-OpmH triclosan extrusion system of Pseudomonas aeruginosa and the ZrpADBC pump of Serratia sp. ATCC 39006 (Mima et al, 2007;Gristwood et al, 2008;Weeks et al, 2015). Alternatively, it is possible that Sll0141 and Sll0180 are active in yet undescribed mechanisms that indirectly affect the T1SS.…”
Section: Tolc-mediated Protein Secretionmentioning
confidence: 99%
“…14 One protomer in each dimer is thought to be responsible for the stimulation of transporter turnover, whereas the second protomer is important for functional interactions with TolC (Figure 6). Hence, the oligomerization of AcrA is essential not only for the assembly of the trans-periplasmic drug tunnel but also for the coupling of transport processes in the two different membranes.…”
mentioning
confidence: 99%